2012
DOI: 10.3174/ajnr.a3035
|View full text |Cite
|
Sign up to set email alerts
|

Acute Brain MRI Findings in 120 Malawian Children with Cerebral Malaria: New Insights into an Ancient Disease

Abstract: Background and Purpose There have been few neuroimaging studies of pediatric cerebral malaria (CM), a common, often fatal tropical condition. We undertook a prospective study of pediatric CM to better characterize the MRI features of this syndrome, comparing findings in children meeting a stringent definition of CM to those in a control group who were infected with malaria but who were likely to have a non-malarial cause of coma. Materials and Methods Consecutive children admitted with traditionally defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
124
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 31 publications
6
124
2
Order By: Relevance
“…One of the most deadly complications of P. falciparum infection in humans is cerebral malaria (HCM) characterized by the onset of severe neurological signs such as altered consciousness, seizures, and coma (2). Autopsy and MRI analyses of brains of children with HCM indicate sequestration of infected red blood cells (iRBCs), microhemorrhaging, breakdown of the blood-brain barrier (BBB) (3), and a fatal increase in intracranial pressure resulting from edema (4,5). At present, despite effective antimalarial drug treatment, mortality for children presenting with HCM remains high, at 15-25%.…”
mentioning
confidence: 99%
“…One of the most deadly complications of P. falciparum infection in humans is cerebral malaria (HCM) characterized by the onset of severe neurological signs such as altered consciousness, seizures, and coma (2). Autopsy and MRI analyses of brains of children with HCM indicate sequestration of infected red blood cells (iRBCs), microhemorrhaging, breakdown of the blood-brain barrier (BBB) (3), and a fatal increase in intracranial pressure resulting from edema (4,5). At present, despite effective antimalarial drug treatment, mortality for children presenting with HCM remains high, at 15-25%.…”
mentioning
confidence: 99%
“…Computed tomography of Kenyan children with cerebral malaria revealed that more than 40% had brain edema (7). More recently, increased brain volume in Malawian children with cerebral malaria based on MRI was reported (8). Severe intracranial hypertension in children with cerebral malaria is often fatal (7,9).…”
mentioning
confidence: 99%
“…We previously reported the MRI findings found in 120 children with retinopathy-positive CM scanned during this time interval. 11 In our previous study, scans from children with retinopathy-positive CM were compared with images from 32 children with retinopathy-negative CM.…”
Section: Introductionmentioning
confidence: 99%
“…Criteria have been established for the assessment of overall brain volume. 11 Discrepant interpretations between the radiologists were settled by consensus.…”
mentioning
confidence: 99%